Erythropoiesis Stimulation in Patients with Postoperative Anemia - D. B. Borisov; B. B. Markov; P. A. Mezentsev; I. R. Poskotinov; N. A. Istomina (Общая реаниматология, 2013)
Early treatment for anemia with epoietin (EPO) and intravenous iron after replacement of the large lower extremity joints permits an 8 g/l increment in hemoglobin concentration to be achieved by postoperative day 10 versus day 2. Objective: to evaluate the efficiency of medical stimulation of erythropoiesis in the treatment of anemia after large joint replacement. Materials and methods. The medical records of patients who had undergone hip or knee joint replacement in January 2010 to August 2011 were retrospectively analyzed. Group 1 (EPO group) included 32 patients who postoperatively received iron saccharate 600 mg and subcutaneous epoietin alfa 40,000 IU. In Group 2 (IRON group), 27 patients took iron saccha-rate 600 mg without epoietin. In Group 3 (CON group) 62 patients had no parenteral erythropoietic stimulants. Blood hemoglobin levels on postoperative days 1, 2, and 10 were a main control indicator. Blood transfusion therapy was not performed in the identified groups. Results. In the first two days, hemoglobin levels were statistically significantly higher in the CON group than those in the EPO group and on day 10 intergroup differences were absent. By day 10 versus day 2, a statistically significant increase in hemoglobin concentrations was found in the EPO and IRON groups. In the EPO group, the hemoglobin concentration increment was significantly higher than that in the CON group. There were no clinical signs of thrombosis and thromboembolic events in the patients of the study groups. Conclusion. The co-administration of intravenous iron and epoietin enables an 8 g/l increase to be achieved on postoperative day 10 versus day 2. Key words: joint replacement, anemia, epoietin, iron saccharate, intravenous iron.